Assessing Personality–Situation Interplay in Personnel Selection: Toward More Integration into Personality Research. Issue 5 (September 2017) - Lievens, Filip
Over the years, the personnel selection field has developed methods to assess trait expression in particular situations, but these approaches have evolved mostly outside the field of personality psychology. In this article, I review available personnel selection evidence regarding two such approaches: (i) situational judgement tests that present short scenarios and ask job candidates how they would handle the situations and (ii) assessment centre exercises requiring candidates to display behaviour in specified interactive situations. I describe these approaches and discuss their relations with personality research. I posit that adapting these approaches to personality research creates methodological diversity to address key research themes related to within–person variability, trait–behaviour links, personality disorders, and personality expression and perception. Copyright © 2017 European Association of Personality Psychology